SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0014
|View full text |Cite
|
Sign up to set email alerts
|

Heat of Vaporization and Species Evolution during Gasoline Evaporation Measured by DSC/TGA/MS for Blends of C1 to C4 Alcohols in Commercial Gasoline Blendstocks

Abstract: Evaporative cooling of the fuel-air charge by fuel evaporation is an important feature of direct-injection spark-ignition engines that improves fuel knock resistance and reduces pumping losses at intermediate load, but in some cases, may increase fine particle emissions. We have reported on experimental approaches for measuring both total heat of vaporization and examination of the evaporative heat effect as a function of fraction evaporated for gasolines and ethanol blends. In this paper, we extend this work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…One example of such an interaction would be a high-HOV component (i.e., C1 to C4 alcohols) causing cooling that slows the evaporation of high-boiling aromatics. Because solutions of these alcohols in hydrocarbons are thermodynamically nonideal-their vapor-liquid equilibrium is not well described by Raoult's law-there may be other effects such as suppression of aromatic evaporation until the alcohol is evaporated [120,121]. There may be other interactions affecting fuel evaporation as well [34].…”
Section: Basic Research Needsmentioning
confidence: 99%
“…One example of such an interaction would be a high-HOV component (i.e., C1 to C4 alcohols) causing cooling that slows the evaporation of high-boiling aromatics. Because solutions of these alcohols in hydrocarbons are thermodynamically nonideal-their vapor-liquid equilibrium is not well described by Raoult's law-there may be other effects such as suppression of aromatic evaporation until the alcohol is evaporated [120,121]. There may be other interactions affecting fuel evaporation as well [34].…”
Section: Basic Research Needsmentioning
confidence: 99%
“…In 2015, the United States Department of Energy initiated a multi-laboratory and multi-year effort to co-optimize fuels and engines known as the Co-Optimization of Fuels and Engines Initiative (Co-Optima). 10,11 Early activities included identifying potential fuel candidate molecules to be evaluated for their combustion, chemistry, and compatibility properties with current and advanced engine concepts. One of these early studies identified over 35 biomass-derived blendstock compounds, which included several ketones.…”
Section: Introductionmentioning
confidence: 99%